Effect of Different Circuit Training on Cardiovascular Responses in Cirrhotic Patients - Nasser, Igor; Willardson, Jeffrey; de Mello Perez, Renata; Reis, Michel Silva; de Azevedo Brito, Anderson; Dias, Ingrid Ferreira; Miranda, Humberto Lameira (International Journal of Sports Medicine, 2019)
The purpose of this study was to analyze and compare heart rate (HR), heart rate variability (HRV), and blood pressure (BP) responses during and after circuit resistance training with 1 min. (CIR1) vs. 2 min. (CIR2) rest intervals between exercises in liver cirrhosis patients. 10 patients (7 women, 3 men) participated in 2 experimental sessions (CIR1 and CIR2) in random order. Each experimental session consisted of 6 exercises performed for 3 sets of 10 repetitions with 70% of the 10-RM load. The only difference between experimental sessions was taking either 1 min. (CIR1) or 2 min. (CIR2) of rest between exercises. Prior and during each session, BP, HR and HRV (beat-to-beat intervals) were assessed. Training efficiency were significant higher for CIR1 when compared to CIR2, since same total training volume was performed in less time. Both protocols elicited significant changes in HR, SBP, and SampEn. Based on the ∆HR and ∆IRR between protocols, higher cardiovascular stress was observed for CIR1 vs. CIR2. However, the patients presented a similar recovery pattern between experimental sessions, and did not present significant alterations in the HRV at 60 min post-workout. In summary, the fast adjustment of autonomic modulation in HRV and BP suggests that circuit resistance training with 1-min or 2-min rest intervals between exercises elicits typical cardiovascular responses in liver cirrhosis patients.
Keywords: strength training; circuit-based exercises; heart rate variability; blood pressure; liver cirrhosis